Establishment of Functional Liver Spheroids From Human Hepatocyte-Derived Liver Progenitor-Like Cells for Cell Therapy - Liu, Wen-Ming; Zhou, Xu; Chen, Cai-Yang; Lv, Dong-Dong; Huang, Wei-Jian; Peng, Yuan; Wu, Hong-Ping; Chen, Yi; Tang, Dan; Guo, Li-Na; Wang, Xiu-Li; Zhang, Hong-Dan; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Globally, about 2 million people die from liver diseases every year. Liver transplantation is the only reliable therapy for severe end-stage liver disease, however, the shortage of organ donors is a huge limitation. Human hepatocytes derived liver progenitor-like cells (HepLPCs) have been reported as a novel source of liver cells for development of in vitro models, cell therapies, and tissue-engineering applications, but their functionality as transplantation donors is unclear. Here, a 3-dimensional (3D) co-culture system using HepLPCs and human umbilical vein endothelial cells (HUVECs) was developed. These HepLPC spheroids mimicked the cellular interactions and architecture of mature hepatocytes, as confirmed through ultrastructure morphology, gene expression profile and functional assays. HepLPCs encapsulated in alginate beads are able to mitigate liver injury in mice treated with carbon tetrachloride (CCL4), while alginate coating protects the cells from immune attack. We confirmed these phenomena due to HUVECs producing glial cell line-derived neurotrophic factor (GDNF) to promote HepLPCs maturation and enhance HepLPCs tight junction through MET phosphorylation. Our results display the efficacy and safety of the alginate microencapsulated spheroids in animal model with acute liver injury (ALF), which may suggest a new strategy for cell therapy.